Papers, 1813-1919 - Liddell family (Plantation records ;, 1973)
Planters of Elmsley Plantation, Woodville, Wilkinson County, Mississippi and Llanada Plantation, near Trinity, Catahoula Parish, Louisiana. Bulk of the material is that of St. John Richardson Liddell, son of Moses Liddell. Papers consist of plantation records, personal correspondence, business and legal papers, account books, notebooks, and plantation diaries.